Transnational Korean Television: Cultural Storytelling and Digital Audiences - Ju, Hyejung (Lexington Books, 2020)
Transnational Korean Television: Cultural Storytelling and Digital Audience provides previously absent analyses of Korean TV dramas' transnational influences, peculiar production features, distribution, and consumption to enrich the contextual understanding of Korean TV's transcultural mobility. Even as academic discussions about the Korean Wave have heated up, Korean television studies from transnational viewpoints often lack in-depth analysis and overlook the recently extended flow of Korean television beyond Asia. This book illustrates the ecology of Korean television along with the Korean Wave for the past two decades in order to showcase Korean TV dramas' international mobility and its constant expansion with the different Western television and their audiences. Korean TV dramas' mobility in crossing borders has been seen in both transnational and transcultural flows, and the book opens up the potential to observe the constant flow of Korean television content in new places, peoples, manners, and platforms around the world. Scholars of media studies, communication, cultural studies, and Asian studies will find this book especially useful.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

India Talking: Politics, Democracy and News Television - Mehta, Nalin (Television in India: Satellites, Politics and Cultural Change, 2008)
After four decades of state monopoly over television Indian viewers gottheir first taste of private television in the early 1990s. By 1998, the first of India’s private 24-hour news channels was on the airwaves and by 2007more than 300 satellite channels were broadcasting into Indian homes. Ofthese, 106 broadcast news in 14 languages and as many as 54 of these were24-hour news channels in 11 languages.1 These are conservative figures thatdo not include many foreign and local cable networks that also broadcastnews.2 Even so, the numbers are a stark illustration of how the Indian statelost control over television broadcasting despite its best efforts to the con-trary. No other country in the world has such a concentration of private news channels as India. The creation of a television public has significantimplications for democracy and this essay focuses on what 24-hour newsmeans for India. It argues that the emergence of television news networkshas greatly enhanced and strengthened deliberative Indian democracy.Commercial mass media stands at the junction of politics and the economy,enabling the entry of citizens onto the stage of politics, while simultaneouslyseeking to appropriate that energy for its own commercial benefit (Rajago-pal, 1999: 133). This is a claim that needs to be differentiated from the usual journalistic self-image of the fourth estate acting as vigilant defenders ofdemocratic ideals. That notion should not be romanticised too muchbecause news production itself is a cultural process that cannot be separatedfrom its social environment. News producers always function under certaininstitutional constraints that are endemic to the news-gathering process.Leftist and liberal scholars of the media differ in their emphasis but allagree that news production is always circumscribed by institutional filters.3News is ‘more a pawn of shared suppositions than the purveyor of selfconscious messages’ (Schudson, 1995: 15). Yet, the media are important,and while it is difficult to draw direct causal linkages, there is no doubt thatthey initiate and create a new sphere of political action.
Num Pages: 30
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Spaces of Television: Rethinking the Public/Private Divide in Postcolonial India - Kumar, Shanti (Channeling Cultures: Television Studies from India, 2014)
This chapter critically evaluates changing definitions of ‘public’ in Indian television in relation to discourses of globalization and media privatization. It examines the debate over the nationalist agenda of public broadcasting in India in relation to the demands for alternative models of broadcasting, and the rise of private commercial satellite channels since the 1990s. It also discusses how representations of traditionally private desires of sexuality and intimacy in soap operas, reality TV shows and music television are redefining the public in India. It outlines the ways in which private desire is made visible — and thus made public — through the convergence of the television screen, the cinematic screen, the computer screen, and the mobile screen. It argues that binaries of ‘public’ versus ‘private’ force us into either/or debates even though such category systems are always-already hybrid in postcolonial societies such as India.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television in Post-Reform Vietnam: Nation, Media, Market - Nguyen-Thu, Giang (Routledge, 2018)
This book explores Vietnamese popular television in the post-Reform era, that is, from 1986, focussing on the relationship between television and national imagination. It locates Vietnamese television in the experiences of everyday life and the prevailing network of power relations resulting from marketization and globalization, and, as such, moves beyond the clichéd assumption of Vietnamese media as a mere propagandist instrument of the party state. With examples from a wide range of television genres, the book demonstrates how Vietnamese television enables novel conditions of cultural oppression as well as political engagement in the name of the nation. In sharp contrast to the previous image of Vietnam as a war-torn land, post-Reform television conjures into being a new sense of national belonging based on an implicit rejection of the socialist past, hopes for peace and prosperity, and anxieties about a globalized future. This book highlights the richness of Vietnam’s current culture and identity, characterized, the book argues, by ‘fraternity without uniformity’.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Australie (lieu de production du savoir); Vietnam (corpus analysé); _Nettoyé

Women, Television and Everyday Life in Korea: Journeys of Hope - Kim, Youna (Taylor & Francis Group, 2006)
Fusing audience research and ethnography, the book presents a compelling account of women's changing lives and identities in relation to the impact of the most popular media culture in everyday life: television. Within the historically-specific social conditions of Korean modernity, Youna Kim analyzes how Korean women of varying age and class group cope with the new environment of changing economical structure and social relations. The book argues that television is an important resource for women, stimulating them to research their own lives and identities. Youna Kim reveals Korean women as creative, energetic and critical audiences in their responses to evolving modernity and the impact of the West. Based on original empirical research, the book explores the hopes, aspirations, frustrations and dilemmas of Korean women as they try to cope with life beyond traditional grounds. Going beyond the traditional Anglo-American view of media and culture, this text will appeal to students and scholars of both Korean area studies and media and communications studies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); France (lieu de production du savoir); _Nettoyé

Refashioning Chinese Television Through Digital Fun - Bai, Ruoyun (The Routledge Companion to Global Television, 2019)
This chapter discusses how Chinese television has been refashioned by the digital entertainment industry, and contends that new genres, identities, and representations have emerged in recognition of youths as the most valuable and desirable category of audience. It does so by way of three case studies. The first illustrates the symbiotic relationship between online literature and television drama production, and how the former contributes to the fantastical turn of Chinese television. The second seeks to understand the emergence of new cultural figures of “supreme heroine” and “sweet males” in the context of the rise of female fandom in contemporary Chinese popular culture. The third reveals how traditional television content, or in this case a political drama, may be recreated by online distributors and influencers so as to be aligned with the habits, attitudes, and preferences of the younger audiences. The chapter concludes that to understand contemporary Chinese television culture, the Internet and social media must become an integral component of inquiry because of their powerful remediating role in the public communication of any cultural text.
Num Pages: 12
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Identités diasporiques; Canada (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Idol Worship: Ethnicity and Difference in Global Television - Sen, Biswarup (Global Television Formats: Understanding Television Across Borders, 2012)
The worldwide success of the Idol format may not require any explanation. We live under the ubiquitous sign of globalization; and hence it should come as no surprise that mass media— which together constitute an ecumenical vehicle of culture with an insatiable appetite for proﬁt— would generate forms (or formats) of art that travel with ease and are translatable into every context. The reception of these formats is, at one level, as unproblematic as its dissemination. To be global (and who isn’t?) is to be eagerly accepting of certain languages, technologies, discourses and styles. The craze surrounding competitive singing can then be explained as one more instance of borders proving permeable to the formulas of international popular culture. It is my argument that in order to understand the unique valence and signiﬁcance of global formats, we need to go beyond issues of production, distribution and reception, and focus instead on the phenomena that arise from their instantiation . This is so because implementing a format in a speciﬁc context has consequences that are neither written into the “program” nor purely derivable from local conditions. Let me provide an illustration. The call-in talk show has recently become a staple on Indian television. The format and content of these shows would be familiar to most Western viewers— a regular host, one or more “experts” discussing politics and culture, and a ﬁnal segment devoted to phone calls from the public.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Asie du sud (corpus analysé); Inde (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

“Citizen Journalism” in the Syrian Uprising: Problematizing Western Narratives in a Local Context - Al-Ghazzi, Omar (Communication Theory, 2014)
This article analyzes the term ‘citizen journalism’ against the backdrop of the Arab uprisings in order to show how it overlooks the local context of digital media practices. The first part examines videos emanating from Syria to illustrate how they blur the lines between acts of witnessing, reporting, and lobbying, as well as between professional and amateur productions, and civic and violent intentions. The second part highlights the genealogies of citizenship and journalism in an Arab context and cautions against assumptions about their universality. The article argues that the oscillation of Western narratives between hopes about digital media's role in democratization in the Arab World and fears about their use in terrorism circumscribe the theorization of digital media practices.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/comt.12047
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

The Other in South Asian Religion, Literature and Film: Perspectives on Otherism and Otherness - Dimitrova, Diana (Routledge, 2013)
This book introduces the term "otherism" and looks at the discourse of otherism and the issue of otherness in South Asian religion, literature and film. It examines cultural questions related to the human condition of being the "other," of the process of "othering" and of the representation of "otherness" and its religious, cultural and ideological implications. The book applies the perspectives of ideological criticism, theories of hybridity, orientalism, nationalism, and gender and queer studies to gain new insights into the literature, film and culture of South Asia. It looks at the different ways of interpreting "otherness" today. The book goes on to analyze the ideological implications of the creation of "otherness" with regard to religious and cultural identity and the legitimation of power, as well as how the representation of "otherness" reflects the power structures of contemporary societies in South Asia. Offering a well-thought-out reflection on important cultural questions as well as a deep insight into the study of religion and "otherness" in South Asian literature and film, this book is a pioneering project that is of interest to scholars of South Asian Studies and South Asian religions, literatures and cultures.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Beyond Bollywood: the Cultural Politics of South Asian Diasporic Film. - Desai, Jigna (Taylor & Francis, 2004)
Beyond Bollywood is the first comprehensive look at the emergence, development, and significance of contemporary South Asian diasporic cinema. From a feminist and queer perspective, Jigna Desai explores the hybrid cinema of the 'Brown Atlantic' through a close look at films in English from and about South Asian diasporas in the United States, Canada, and Britain, including such popular films as My Beautiful Laundrette, Fire, Monsoon Wedding, and Bend it Like Beckham.
OCLC: 824549185
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé